(untitled) (Majalah Kedokteran Bandung, 2021)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Spinal TB is associated with poor functional outcomes. Histopathological examination requires a long waiting times to obtain the results thus impractical for screening and may delay diagnosis. GeneXpert offers rapid tests for prompt screening and diagnosis. This study aimed to assess the diagnostic accuracy of GeneXpert in patients with spinal TB when compared to the histopathology test as the gold standard. This study was performed on patients in the Spine Clinic of the Department of Orthopedic and Traumatology, Dr. Hasan Sadikin General Hospital Bandung who were diagnosed with spinal TB during the period of May 2019–May 2020. Blood samples were collected from the patients and tested using GeneXpert and histopathological assessment. Results demonstrated 34 patients with a positive result and 6 patients with negative results on both diagnostic methods. Twenty nine out of 40 patients (72.5%) had rifampin-sensitive TB. Diagnostic accuracy of GeneXpert, when compared to histopathological examination, is represented by the sensitivity of 88.2%, specificity of 33.3%, positive predictive value of 88.2%, and negative predictive value of 33.3%. High sensitivity results forpatients with spinal TB on GeneXpert suggests that the test is appropriate to be used as a screening method and as a high-yield rapid diagnostic test for patients suspected for spinal TB.